(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Oxide samples with chemical composition La4-xBaxNi3O10+δ, where 0≤x≤2, related to Ruddlesden-Popper phases were synthesized by coprecipitation method of components from nitrates solutions by 0.25 M K2CO3 solution with following calcination of obtained blend by 950оС during 100 hours. X-ray phase analysis of the obtained samples show that the substitution of lanthanum on barium with 0<x≤ 0.5 leads to formation of orthorombic solid solutions, space group Fmmm. At this range of substitution the mean nickel oxidation degree reduces from +2.68 to 2.29. It was shown that when La3+is substituted by Ba2+in RPP with n=3 (La4Ni3O10) transition to RPP n=1 (La2NiO4) takes place with separation of NiO and oxygen. For the first time a research of resistive properties of the obtained complex oxide compounds in low-temperature areas took place; oxygenic nonstoichiometry was determined; analyzed phase composition of the system La4-xBaxNi3O10+δ (0≤x≤2). Study of electrical conductivity shows that the increasing of barium content changes the conduction type from metal (x=0) to semiconductor (x=0,25, x=0,5). This trend of conductivity change can be explained by substitution of lanthanum that has f-electron shell on barium (with bigger ionic radius), which is p-element and the decreasing of the mean nickel oxidation degree by the increasing of substitution degree. Therefore electrical conductivity of mixed oxides in La-Ba-Ni-O system with Ruddlesden-Popper phase structure depends on the Ni3+content and essentially depends on the conductivity electron concentration in the unit cell. The change of conductivity may be caused by the cationic vacancy formation in obtained Ruddlesden-Popper phases and the replacing of more conducting lanthanum-oxygen layers on less conducting barium-oxygen.